Utilizing non-histological serological markers in the prediction of recurrence and metastasis in head and neck melanoma (Ukrainian Journal of Ophthalmology, 2024)
There is a need for the development of additional prognostic melanoma (e.g., head and neck melanoma) biomarkers to stratify melanoma patients and reliably identify high-risk subgroups with the aim of providing effective personalized therapy.Biomarkers play an important role in the diagnosis and prognostic classification of various types of cancer and may be indicators of biological or pathological processes or responses to exposure or intervention, providing a physician with the data helpful for future decision making with regard to patient management.The advent of novel treatments and modalities for treating various stages of the disease with a notable objective response-to-survival ratio gave us good reason, in this review, to emphasize non-histological serological biomarkers for the correction and improvement in the efficacy of treatment as well as the prognosis of survival in patients with head and neck melanoma.
Keywords: melanoma; biomarkers; dermatoscopy; metastases; calcium-binding protein; melanoma inhibitory activity; hepatocyte growth factor; eosinophil cationic protein; serum indoleamine 2; 3-dioxygenase; vitamin D; lactate dehydrogenase